Differential effects of mechano‐electric feedback mechanisms on whole‐heart activation, repolarization, and tension - Gerach, Tobias; Loewe, Axel (The Journal of physiology, 2024)
The human heart is subject to highly variable amounts of strain during day‐to‐day activities and needs to adapt to a wide range of physiological demands. This adaptation is driven by an autoregulatory loop that includes both electrical and the mechanical components. In particular, mechanical forces are known to feed back into the cardiac electrophysiology system, which can result in pro‐ and anti‐arrhythmic effects. Despite the widespread use of computational modelling and simulation for cardiac electrophysiology research, the majority of in silico experiments ignore this mechano‐electric feedback entirely due to the high computational cost associated with solving cardiac mechanics. In this study, we therefore use an electromechanically coupled whole‐heart model to investigate the differential and combined effects of electromechanical feedback mechanisms with a focus on their physiological relevance during sinus rhythm. In particular, we consider troponin‐bound calcium, the effect of deformation on the tissue diffusion tensor, and stretch‐activated channels. We found that activation of the myocardium was only significantly affected when including deformation into the diffusion term of the monodomain equation. Repolarization, on the other hand, was influenced by both troponin‐bound calcium and stretch‐activated channels and resulted in steeper repolarization gradients in the atria. The latter also caused afterdepolarizations in the atria. Due to its central role for tension development, calcium bound to troponin affected stroke volume and pressure. In conclusion, we found that mechano‐electric feedback changes activation and repolarization patterns throughout the heart during sinus rhythm and lead to a markedly more heterogeneous electrophysiological substrate. Key points The electrophysiological and mechanical function of the heart are tightly interrelated by excitation–contraction coupling (ECC) in the forward direction and mechano‐electric feedback (MEF) in the reverse direction. While ECC is considered in many state‐of‐the‐art computational models of cardiac electromechanics, less is known about the effect of different MEF mechanisms. Accounting for calcium bound to troponin increases stroke volume and delays repolarization. Geometry‐mediated MEF leads to more heterogeneous activation and repolarization with steeper gradients. Both effects combine in an additive way. Non‐selective stretch‐activated channels as an additional MEF mechanism lead to heterogeneous diastolic transmembrane voltage, higher developed tension and delayed repolarization or afterdepolarizations in highly stretched parts of the atria. The differential and combined effects of these three MEF mechanisms during sinus rhythm activation in a human four‐chamber heart model may have implications for arrhythmogenesis, both in terms of substrate (repolarization gradients) and triggers (ectopy). figure legend Whole‐heart electrophysiology is affected in several ways by mechano‐electric feedback. Incorporating the mechanical deformation gradient into the monodomain equation alters tissue conductivity, ultimately resulting in a depolarization pattern that is more heterogeneous and leads to steeper repolarization gradients. Non‐selective stretch‐activated channels lead to a more heterogeneous diastolic transmembrane voltage and delayed repolarization or afterdepolarizations depending on the amount of stretch the tissue experiences. Accounting for calcium bound to troponin extends repolarization time, leading to an increase in calcium availability and larger stroke volumes. These mechanisms, when combined, may have implications for arrhythmogenesis relating to triggers and substrate.